2021
DOI: 10.1177/10742484211014162
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide–cGMP Pathway Modulation in an Experimental Model of Hypoxic Pulmonary Hypertension

Abstract: Manipulation of nitric oxide (NO) may enable control of progression and treatment of pulmonary hypertension (PH). Several approaches may modulate the NO-cGMP pathway in vivo. Here, we investigate the effectiveness of 3 modulatory sites: (i) the amount of l-arginine; (ii) the size of plasma NO stores that stimulate soluble guanylate cyclase; (iii) the conversion of cGMP into inactive 5′-GMP, with respect to hypoxia, to test the effectiveness of the treatments with respect to hypoxia-induced PH. Male rats (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…There is no consensus regarding the effect of CSH on the plasma levels of NO metabolites (nitrites and nitrates; NOx), which are typically measured as an index of overall vascular NO bioavailability [ 29 ]. While Fagan et al [ 62 ] reported that 10 days of CSH in rats reduced the plasma nitrate concentration from 6 to 4.5 mM, Bagali et al [ 63 ] found a fall in plasma NOx in rats subjected to 21 days of CSH and Reinero et al [ 64 ] saw no significant change in plasma NOx after 14 days of CSH. In agreement with this study, we also found no changes in the level of plasma NOx.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus regarding the effect of CSH on the plasma levels of NO metabolites (nitrites and nitrates; NOx), which are typically measured as an index of overall vascular NO bioavailability [ 29 ]. While Fagan et al [ 62 ] reported that 10 days of CSH in rats reduced the plasma nitrate concentration from 6 to 4.5 mM, Bagali et al [ 63 ] found a fall in plasma NOx in rats subjected to 21 days of CSH and Reinero et al [ 64 ] saw no significant change in plasma NOx after 14 days of CSH. In agreement with this study, we also found no changes in the level of plasma NOx.…”
Section: Discussionmentioning
confidence: 99%
“…NO generally stabilizes hypoxia-inducible factor (HIF) 1α, which upregulates protein kinase G (PKG) signaling to stimulate secretion of VEGF and other angiogenesis-related growth factors. 43,44 To prove this angiogenesis-related pathway by NO, the gene expression level of NO inducible angiogenic factors were comparatively analyzed depending on the use of disulfide bonding group with GSH and SNAP. As an exogenous NO donor, the disulfide bonding group-derived NO could activate HIF 1α, which resulted in the serial upregulation of PKG, VEGF, HGF, and CD31 (Fig.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…The nitric oxide–cyclic guanosine 3′,5′-monophosphate (NO-cGMP) pathway ( Garmaroudi et al, 2016 ; Mónica et al, 2016 ; Carlström, 2021 ) is central for maintaining and sustaining vasodilation ( Böger and Hannemann, 2020 ), vasculature ( Costa et al, 2021 ), and vascular function ( Golshiri et al, 2020 ), as reduced nitric oxide bioavailability can cause endothelial dysfunction ( Münzel et al, 2021 ; Boughaleb et al, 2022 ), vasoconstriction ( Bank et al, 1994 ; Hannemann and Böger, 2022 ), and hypoxia ( Reinero et al, 2021 ; Gajecki et al, 2022 ). Sex hormones, such as testosterone, are linked to the NO-cGMP pathway ( Andric et al, 2010 ), indicating an interdependent relationship between testosterone (androgen) and nitric oxide levels ( Hotta et al, 2019 ; Gur et al, 2020 ; Zabbarova et al, 2022 ), which can be related to fluctuations in oxygen perfusion bioavailability ( Soni and Padwad, 2017 ; Nascimento-Filho et al, 2022 ).…”
Section: Middle-aging Hypovascularity Hypoxia Hypothesis Patternsmentioning
confidence: 99%